2017
DOI: 10.1007/s12550-017-0281-2
|View full text |Cite
|
Sign up to set email alerts
|

Rising atmospheric CO2 concentration may imply higher risk of Fusarium mycotoxin contamination of wheat grains

Abstract: Increasing atmospheric CO2 concentration not only has a direct impact on plants but also affects plant-pathogen interactions. Due to economic and health-related problems, special concern was given thus in the present work to the effect of elevated CO2 (750 μmol mol -1 ) level on the Fusarium culmorum infection and mycotoxin contamination of wheat. Despite the fact that disease severity was found to be not or little affected by elevated CO2 in most varieties, as the spread of Fusarium increased only in one vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Cuperlovic-Culf et al 45 demonstrated that the effects of e[CO 2 ] on FHB and DON contamination were dependent on both F. graminearum strain and wheat variety, underlining that moderately resistant lines may become significantly more susceptible to mycotoxin accumulation when infected by certain F. graminearum strains at e[CO 2 ]. Similarly, Bencze et al 44 and Vaŕy et al 46 observed variable effects of elevated CO 2 on head blight between wheat varieties and suggested that CO 2 has the potential to directly affect not only the fungal pathogen or the host plant but also the plant−pathogen interactions. Conversely, Vaughan et al 47 reported that e[CO 2 ] increased maize susceptibility to Fusarium verticillioides proliferation, while fumonisin levels were unaltered.…”
Section: ■ Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Cuperlovic-Culf et al 45 demonstrated that the effects of e[CO 2 ] on FHB and DON contamination were dependent on both F. graminearum strain and wheat variety, underlining that moderately resistant lines may become significantly more susceptible to mycotoxin accumulation when infected by certain F. graminearum strains at e[CO 2 ]. Similarly, Bencze et al 44 and Vaŕy et al 46 observed variable effects of elevated CO 2 on head blight between wheat varieties and suggested that CO 2 has the potential to directly affect not only the fungal pathogen or the host plant but also the plant−pathogen interactions. Conversely, Vaughan et al 47 reported that e[CO 2 ] increased maize susceptibility to Fusarium verticillioides proliferation, while fumonisin levels were unaltered.…”
Section: ■ Discussionmentioning
confidence: 95%
“…All the cultivars compared in our study can be classified as moderately resistant to DON contamination. Previous investigations, such as those recently reported by Bencze et al 44 and Cuperlovic-Culf et al, 45 were carried out in controlled conditions (greenhouse or phytotron) and on F. graminearum-or F. culmorum-inoculated wheat. Cuperlovic-Culf et al 45 demonstrated that the effects of e[CO 2 ] on FHB and DON contamination were dependent on both F. graminearum strain and wheat variety, underlining that moderately resistant lines may become significantly more susceptible to mycotoxin accumulation when infected by certain F. graminearum strains at e[CO 2 ].…”
Section: ■ Discussionmentioning
confidence: 99%
“…The impact of elevated CO 2 on grain quality is cultivar dependent, and even known adaptive traits, such as high nitrogen use efficiency and improved root vigor, are not sufficient to counteract the effects on grain protein and recover end-use quality 19 , 20 . The effects of rising CO 2 not only impacts wheat nutritional content but can also increase plant disease susceptibility, particularly to FHB 3 , 21 – 23 . The combined adverse effects of elevated CO 2 on wheat nutritional content and disease susceptibility is a significant threat to wheat producers and consumers.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a certain correlation between CO 2 levels in the atmosphere and mycotoxin production [19]. Determining the influence of climate on mycotoxin and other toxin production is a complex task, since the production of different toxins is influenced differently by the same weather conditions, as can be seen from this research.…”
Section: Resultsmentioning
confidence: 90%